2005
DOI: 10.1007/s00468-005-0411-x
|View full text |Cite
|
Sign up to set email alerts
|

Origin identification of Pinus nigra populations in southwestern Europe using terpene composition variations

Abstract: The geographical variation of terpenes of Pinus nigra populations from southwestern Europe was studied. Terpenes from the foliage of 16 populations from Corsica, Herault (France) and the East Pyrenees (France and Spain) were analyzed. A total of 42 terpenes were detected, with α-pinene the dominant monoterpene and germacrene-d and caryophyllene the dominant sesquiterpenes. The differences in quantitative content of selected compounds clearly divide populations into two basic geographical groups: on one side th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
12
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 26 publications
4
12
0
Order By: Relevance
“…Trimethylsilyl diterpenoid resin acids (pimaric, levopimaric, isopimaric, palustric, dehydroabietic, abietic, and neoabietic acids) were detected in the PLW extract solvent. Several types of terpenoids detected in PLW in this study agree with reported terpenoids found in other pine sources (Nerg et al, 1994;Manninen et al, 2002;Bojovic et al, 2005;Ormeño et al, 2007;Bohlmann and Keeling, 2008;Rodrigues-Corrêa et al, 2012;Achotegui-Castells et al, 2013) and show some similarities with terpenoids present in spruce (Martin et al, 2002;Zhao et al, 2010). For example, the most abundant monoterpenes extracted from PLW were in agreement with the most abundant monoterpenes present in pine wood and foliage, being α-and β-pinene.…”
Section: Terpenoid Content Of Pine Lighter Woodsupporting
confidence: 89%
See 3 more Smart Citations
“…Trimethylsilyl diterpenoid resin acids (pimaric, levopimaric, isopimaric, palustric, dehydroabietic, abietic, and neoabietic acids) were detected in the PLW extract solvent. Several types of terpenoids detected in PLW in this study agree with reported terpenoids found in other pine sources (Nerg et al, 1994;Manninen et al, 2002;Bojovic et al, 2005;Ormeño et al, 2007;Bohlmann and Keeling, 2008;Rodrigues-Corrêa et al, 2012;Achotegui-Castells et al, 2013) and show some similarities with terpenoids present in spruce (Martin et al, 2002;Zhao et al, 2010). For example, the most abundant monoterpenes extracted from PLW were in agreement with the most abundant monoterpenes present in pine wood and foliage, being α-and β-pinene.…”
Section: Terpenoid Content Of Pine Lighter Woodsupporting
confidence: 89%
“…Monoterpenes and sesquiterpenes have also been investigated as potential sources of renewable fuel (Monteiro and Veloso, 2004;Harvey et al, 2009;Peralta-Yahya et al, 2011;Renninger et al, 2011;Meylemans et al, 2012;Rodrigues-Corrêa et al, 2012;Hellier et al, 2013;Vallinayagam et al, 2014). Efforts have been made to understand the genetic, ecological, and physicochemical processes behind the production and accumulation of terpenoids in pine and other feedstocks (Nerg et al, 1994;Manninen et al, 2002;Martin et al, 2002;Bojovic et al, 2005;Schmidt et al, 2011;Achotegui-Castells et al, 2013;Susaeta et al, 2014). For this type of research, it is important to accurately measure the terpenoid content in biomass to be able to compare the variables potentially affecting terpenoid production and accumulation.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…-carene in Picea abies [57], bpinene in Pinus nigra [41], etc. Regarding the population diversity of P. omorika, two more compounds with trimodal distribution, i.e., myrcene and (E)-hex-2-enal were used in the present work (Fig.…”
mentioning
confidence: 99%